Patient Preference Studies During Early Drug Development: Aligning Stakeholders to Ensure Development Plans Meet Patient Needs - Cook, Nigel S.; Cave, Julie; Holtorf, Anke-Peggy (Frontiers in Medicine, 2019)
Although patient preferences have been studied broadly for marketed products or around the time of submission to authorities and launch, patient preference studies have rarely been used during the early drug development phases. In this paper, we formulate three hypotheses supporting the use of patient preference studies in early product development: (1) integration of the patient perspective into the development process from phase 1 onwards will result in healthcare solutions with outcomes that best address patients’ needs; (2) a structured process to build patient-based evidence involving partnerships between patients and other key stakeholders will improve alignment of development activities with the needs of patients; (3) quantitative patient preference research built on robust qualitative insights is necessary to strengthen development decisions in the interests of patients. To illustrate such a structured process, we describe qualitative insights research (social media analysis and online bulletin boards) and quantitative patient preference studies in dry eye disease and non-alcoholic steatohepatitis conducted during early product development by a pharmaceutical company to generate patient-based evidence. The outputs from such early patient preference studies are being used to inform patient reported outcome strategies, clinical development strategies, product design and delivery features, and form the basis for early dialog with regulators, health technology assessment (HTA) bodies and payers to ensure focus and alignment on patient-relevant endpoints. Furthermore, to discuss and theoretically substantiate our hypotheses, we review how different groups and organizations are working to embrace fully the patient perspective in product development and healthcare decision-making. The hypotheses are commensurate with the general trend towards patient-centered healthcare and the activities initiated by regulators, HTA agencies, and patient organizations. We advocate that all healthcare players should actively contribute to aligning on best practices concerning choice of methodologies and engage in multi-stakeholder dialog along the entire product development chain, to realize health technologies that best meet the needs of patients.